What are the characteristics and progression of visual field defects in patients with Leber hereditary optic neuropathy: a prospective single-centre study in China. Issue 3 (15th March 2019) - Liu, Hong-Li; Yuan, Jia-Jia; Tian, Zhen; Li, Xin; Song, Lin; Li, Bin
Abstract : Objective: To study the characteristics and progression of visual field defects in patients with Leber hereditary optic neuropathy. Design: Prospective study. Setting: 3-A-class hospital in China; single-centre study. Participants: From 100 patients diagnosed with Leber hereditary optic neuropathy, 80 (160 eyes; 68 men and 12 women; youngest patient, 6 years; oldest patient, 35 years) were recruited. Exposure: All patients were followed up for at least 12 months. Each patient underwent at least three visual field examinations. Patient groups 1–6 were created according to the time of visual field data acquisition. Patient group 7 included patients with a different onset of disease between eyes. Group 8 was composed of patients with a course of disease of 12–24 months when one of the examinations performed. Patients who performed the third examination made up patient group 9. Primary outcome measures: Prevalence of the different visual field defect types on the basis of severity in groups 1–6. Mean of the difference of visual function between eyes in group 7. Result: In groups 1–6, the prevalences of defects classified using Visual Field Index values were significantly different between groups 1 and 3. In group 7, with the prolongation of the course of the disease, the mean of the difference of visual function between eyes decreased. There was no significant correlation between age and the severity of visual field defect. There was significant correlation between visual acuity and the severity of visual field defect. Conclusion: Visual field defects in patients with Leber hereditary optic neuropathy (G11778A) may continuously progress within 6 months of disease development, and remain stable after 9 months. With the progression of the disease, the differences in visual function between eyes may decrease. The severity of visual field defect seems to be independent of age; however, could be related to visual acuity. Trial registration number: NCT03428178, NCT01267422 .